La matematización para la enseñanza-aprendizaje de las leyes de newton y el rendimiento académico en los estudiantes de primero de bgu de la Unidad Educativa Tomas Oleas” del cantón Colta, Provincia de Chimborazo, periodo 2016-2017 - Naranjo Sagñay, William Cristóbal (2017)
The present investigation was carried out in the first year of high school of Tomas Oleas Institute. The greatest interest was the mathematization to teach and learn the laws of Newton the objectives, different mathematical activities were identified to help student improve their academic performance. The research design used was non experimental, the type of research was descriptive, documentary and transversal. For data collection, objective test was used as technique. After the diagnosis, it was evidenced that the greater percentage pf the students do not easily and pertinently solve problems on Newton’s laws. Workshops were carried out where the mathematization was applied to support student and teachers. As a conclusion of this work it was determined that the implementation of mathematics on different problems with Newton’s laws stimulates student to develop skills and in addition problems of Newton’s law exercises were solved. It is necessary to continue working with these tools since they are educational support produced by different means in order to strengthen student learning. We must consider the existing shortcomings in problem solving to work with tools and didactic strategies for a better understanding of Newton’s laws.